PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII5 SMPN 25 PEKANBARU PADA MATERI HIMPUNAN - Melsa, Engla; Syofni, Syofni; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to improve the learning process and the students’ mathematics learning outcomes through implementation of Problem Based Learning (PBL) Model. The type of this research is Classroom Action Research with two cycle. This research was conducted at class VII5 of SMPN 25 Pekanbaru in the odd semester of the academic year 2018/2019. The subject of this research consisted of 40 students. The required data were teacher and students’ activities, collected by observation technique and analyzed by descriptive narrative analysis, and data of the students’ learning outcomes were collected by test and analyzed by descriptive narrative analysis. Statistic descriptive analysis showed that students’ mathematics learning outcomes improved from the basic score to the daily test I, from daily test I to daily test II. The percentage and frequency of students who achieved minimum completeness criteria was increased from the basic score with percentage 37.5% (15 students) to 47.5% (19 students) in the daily test I and 75% (30 students) in the daily test II. This research concluded that the implementation of PBL model improved the learning process and the students’ mathematic learning outcomes at class VII5 of SMPN 25 Pekanbaru in the odd semester of the academic year 2018/2019.Key Words: Problem Based Learning model,Learning Outcomes